Valorization of lemon peel waste as biosorbent for the simultaneous removal of nickel and cadmium from industrial effluents - Villén-Guzmán, María Dolores; Cerrillo-González, María del Mar; Paz-García, Juan Manuel; Rodríguez-Maroto, José Miguel; Arhoun, Brahim (elsevier, 2021)
The valorization of agricultural waste as biosorbent requires studies dealing with aqueous systems containing coexisting heavy metals. Batch adsorption experiments were carried out to study the competitive biosorption of Ni(II) and Cd(II) on alkalimodified lemon peel. The biosorption kinetic analysis indicated that the uptake of Ni(II) on lemon peel was better described by pseudo first-order model whereas for Cd(II) results were no conclusive. A rapid uptake of both metals on alkali-modified lemon peel was detected during the first 10 min obtaining more than 90% of the maximum sorption. The maximum adsorption capacity of Ni(II) and Cd(II) for single metal systems at optimum conditions (pH = 5, S/L = 5 g L−1, 25 ◦C), which were obtained from Langmuir model, reached as high as about 0.626 and 0.726 mmol g−1, respectively. These values were reduced 30 and 20 % in the presence of 100 mg L−1 of Cd and Ni, respectively. Regarding the reusability of the biosorbent, after five consecutives adsorption–desorption cycles using HNO3 and H2SO4 as desorption reagents percentages of 90 and 70 % were recovered for Ni and Cd. The promising results obtained through this work are expected to promote the use of lemon peel as an efficient biosorbent for industrial applications.
Keywords: Residuos agrícolas; Competitive biosorption; Surface modification; Binary system; Lemon peel waste; Ni (II) and Cd (II); Industrial effluents